HUBUNGAN PHYTOPLANKTON DAN ZOOPLANKTON TERHADAP PRODUKTIVITAS KOLAM AGROWISATA UIR KECAMATAN SIAK HULU KABUPATEN KAMPAR PROVINSI RIAU - Muhammad Hasby (UIR Press, 2017)
This study took plankton and water samples carried out in 5 (five) pond plots at several locations in the UIR Agro Tourism pond. Various types of fish are maintained in these ponds. A sampling of water is done once a week starting at 08.00 until 12.30 WIB. The method of sampling is carried out by determining seven points/places in each pool. Based on the results of the study found that there are 34 species of phytoplankton consisting of 3 classes, namely Chlorophyceae (15 species), Cyanophyceae (8 species) and Bacillariophyceae (11 species). The highest abundance of phytoplankton is in pond II, which is 3027 cells / l. and the lowest phytoplankton abundance is at a station I which is 953 cells / l. Zooplankton found 2 classes of zooplankton consisting of 4 species namely Crustacea class consisting of 3 species, and Sarcodina class 1 species. The highest zooplankton abundance in an IV, while the lowest abundance in an I. From multiple regression analysis of phytoplankton obtained Fcount 2.898 <Ftable 2.90 and for zooplankton obtained Fcount 2,074 <Ftable of 2.90, which means no influence some water quality parameters (temperature, brightness, pH, dissolved oxygen, phosphate and nitrate) to plankton abundance at a 95% confidence level. The relationship between plankton and water quality is not very real and not significant. The results of observations of water quality indicate that in general the results of physical-chemical water measurements indicate that the pond waters are still classified as good and can still support the life of organisms in it, especially plankton.